Factores psicosociales que influyen en la conducta agresiva de los estudiantes de bachillerato, del Colegio Carmen Mora de Encalada del cantón Pasaje en el periodo lectivo 2013-2014. - Berrezueta Cedillo, Glenda Maritza (2014)
Thus the proposal is executed, which is to produce a school for parents called Learning Together, whose purpose is to sensitize parents regarding working with children provide effective communication for which the relevant aspects of socialized assertiveness in communication.